كاریگه‌ریی چیرۆك له‌ گه‌شه‌پێدانی به‌های ئاكاریی لای منداڵانی باخچه‌ توێژینه‌وه‌یه‌كی مه‌یدانییه‌ له‌ شاری سلێمانی ئه‌نجامدراوه‌ - صابر, پ.د.نیان نامق; حسین, هێرۆ عبدالله (Sulaimani Journal for Humanities, 2023)
The aim of the study is to determine the consequence (effect) of storytelling on the development of moral values among kindergarten children aged (5-6 years), At the same time, to determine the difference in the level of moral values before and after the experiment according to the variables (age, birth, ranking, gender) for the control group, knowing the difference in the level of moral values before and after the experiment according to the variables (age, birth, ranking, gender) for experimental group, With two assumptions: there is no difference in statistics at the level of documentation (0.05) between the accounting center of the preliminary and retreat tests between the experience and control group before the storytelling, and there is also no statistical difference at the level of evidence (0.05) between the arithmetic means of pre- and post-test scores between the experimental and control groups after storytelling. The researcher used methods to achieve the goal of her research, which is compatible with the content of her research. The research data is the measure of moral values that consists of (5) field and the preparation of stories specified to the field of moral values, which are (5) stories, The research community includes kindergarten children, the sample of the study is (20) children divided into two groups, the experience group (20) children and controlled groups (20) children, total number are (40) children, due to statistical tools. and reached several conclusions, including: The difference between the levels of the research criteria for the initial and final tests of the criteria for the experimental group in the field of (integrity, helpfulness, obedience, kindness, protection) is in favor of the final test of children's storytelling values. To determine the differences in the level of moral values before and after the experiment according to the variables (age, ranking, gender) for the control group, and in the experimental group the variables are equal and there are no differences. No differences are observed for the difference between the scores of both the pre- and post-tests of the controlled experimental group before storytelling. For the difference between the scores of both the pre- and post-tests of the controlled experimental group after storytelling, there is a difference that is in favor of the experimental group for storytelling.
Keywords: childrens story; moral value; kindergarten